A double‐blind, placebo‐controlled, single‐ascending dose study to evaluate the safety, tolerability, pharmacokinetics, and pharmacodynamics of HM15136, a novel long‐acting glucagon analogue, in healthy subjects. Issue 3 (24th November 2021) - Huh, Ki Young; Hwang, Jun Gi; Shin, Wonjung; BAEK, Seungjae; Choi, JaeDuk; Lee, Nora; Cho, Young Min; Lee, Howard
Abstract: Aim: To evaluate the safety and tolerability, pharmacokinetics, and pharmacodynamics of HM15136, a novel long‐acting glucagon analogue under development, in healthy males and females presenting with no childbearing potential. Materials and Methods: A randomized, double‐blind, placebo‐controlled, single‐ascending dose study was conducted in 56 subjects who randomly received a single subcutaneous dose of HM15136 or its matching placebo at a ratio of 6:2 at 10, 20, 30, 50, 80, 100, and 120 μg/kg. Results: All adverse events were mild and transient. Neither serious adverse events nor discontinuation as a result of adverse events occurred. The most frequent adverse drug reaction was nausea (5.3%, only in the 100‐ and 120‐μg/kg groups). HM15136, particularly at doses of 50 μg/kg or higher, increased fasting blood glucose, with a maximum increase and area under the curve of 1.5 mmol/L at day 10 ( P  = .006) and 166.3 day·mmol/L ( P  = .022) at the dose of 80 μg/kg, while suppressing the secretion of endogenous glucagon, which continued until day 17. HM15136 also significantly reduced gluconeogenic and ketogenic amino acids. Compensatory changes in endogenous insulin and incretin hormones by HM15136 were not apparent. HM15136 was slowly but steadily absorbed and reached a peak concentration at 46‐68 hours after a single subcutaneous injection. HM15136 was eliminated with a terminal phase half‐life of 77.1‐101.1 hours. Conclusions: A single subcutaneous dose of HM15136 at 10‐120 μg/kg was safe and well tolerated. The long half‐life of HM15136, coupled with an increase in blood glucose for ~2 weeks, may warrant a weekly dosing regimen.